2001
DOI: 10.1017/s1471068400001058
|View full text |Cite
|
Sign up to set email alerts
|

On a theory of probabilistic deductive databases

Abstract: We propose a framework for modeling uncertainty where both belief and doubt can be given independent, first-class status. We adopt probability theory as the mathematical formalism for manipulating uncertainty. An agent can express the uncertainty in her knowledge about a piece of information in the form of a confidence level, consisting of a pair of intervals of probability, one for each of her belief and doubt. The space of confidence levels naturally leads to the notion of a trilattice, similar in spirit to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 46 publications
0
83
0
1
Order By: Relevance
“…An interesting question is whether this approach can shed light on the epistemic content of probabilistic deductive systems, of the kind found in the recent probabilistic deductive database literature [Lukasiewicz 1999;Lakshmanan and Sadri 2001]. Presumably, the ideas developed by Halpern and Pucella [2005] may be applicable in this setting.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting question is whether this approach can shed light on the epistemic content of probabilistic deductive systems, of the kind found in the recent probabilistic deductive database literature [Lukasiewicz 1999;Lakshmanan and Sadri 2001]. Presumably, the ideas developed by Halpern and Pucella [2005] may be applicable in this setting.…”
Section: Resultsmentioning
confidence: 99%
“…A similar relationship between SSAT and other probabilistic logic programming frameworks, e.g., (Ng & Subrahmanian 1992;1993;1994;Dekhtyar & Subrahmanian 2000;Kern-Isberner & Lukasiewicz 2004;Lukasiewicz 1998;Baral, Gelfond, & Rushton 2004;Kersting & Raedt 2000;Lakshmanan & Sadri 2001;Poole 1997;Vennekens, Verbaeten, & Bruynooghe 2004), has not been studied. However, the relationship between the probabilistic logic programming frameworks (Ng & Subrahmanian 1992;1993;1994;Dekhtyar & Subrahmanian 2000;Kern-Isberner & Lukasiewicz 2004;Lukasiewicz 1998) and a different extension to SAT, namely, Probabilistic SAT (PSAT) (Boole 1854) has been studied.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…It was shown that the HPP (Saad & Pontelli 2006) framework is more suitable for reasoning and decision making tasks, including those arising from planning under probabilistic uncertainty (Saad 2007). In addition, it subsumes Lakshmanan and Sadri's (Lakshmanan & Sadri 2001) probabilistic implication-based framework as well as it is a natural extension of classical logic programming with answer set semantics. As a step towards enhancing its reasoning capabilities, the framework of HPP was extended to cope with non-monotonic negation (Saad & Pontelli 2005) by introducing the notion of Normal Hybrid Probabilistic Logic Programs (NHPP) and providing two different semantics namely; stable probabilistic model semantics and wellfounded probabilistic model semantics.…”
Section: Introductionmentioning
confidence: 99%
“…There are approaches which are based either on the structure of lattice (residuated lattice [4,13] or multi-adjoint lattice [9]), or more restrictive structures, such as bilattices or trilattices [7], or even more general structures such as algebraic domains [11]. One can also find some attempts aiming at weakening the restrictions imposed on a (complete) lattice, namely, the "existence of least upper bounds and greatest lower bounds" is relaxed to the "existence of minimal upper bounds and maximal lower bounds".…”
Section: Introductionmentioning
confidence: 99%